Developing a Multi-Representation-Based Physics Mobile Learning to Enhance Critical Thinking and Creative Problem-Solving Skills: A Storyboard - Zakiyah, Sri; Suwarma, Irma Rahma; Rusdiana, Dadi (Universitas Lambung Mangkurat, 2025)
This investigation aims to develop an M-Learning-based learning design for high school pupils in the context of a soundwave lesson specifically to increase critical thinking (CT) skills and creative problem-solving (CPS) ability. This learning media design is created through the ADDIE process, comprising five stages: analysis, design, development, implementation, and evaluation. In this paper, we will elaborate on the analysis and design phases. The analysis phase involves a preliminary examination of the teaching materials necessary for mobile learning. The design stage also involves selecting the proposed prototype's overarching design and creating storyboards. Three of the five subchapters that have been developed have the potential to employ CPS features, while CT features are feasible to integrate into all chapters. These findings suggest that physics mobile learning can be designed to incorporate CT and CPS specifically in the lesson on soundwave.